Salts, solvates and hydrates of the multi-kinase inhibitor drug pazopanib with hydroxybenzoic acids - Rai, Sunil K.; Baidya, Debjani; Nangia, Ashwini K. (Crystengcomm, 2021)
The marketed formulation of pazopanib (PAZ) suffers from low and variable bioavailability because of its poor dissolution rate and photostability issues. The drug falls under Biopharmaceutics Classification System (BCS) class II of low solubility and good permeability. The hydrogen bonds and supramolecular interactions in crystalline forms of PAZ with hydroxybenzoic acids (HBAs) and dihydroxybenzoic acids (DHBAs), as well as its salts are analyzed. Ten X-ray crystal structures of PAZ which include the reference drug, a tetrahydrofuran solvate (PAZ center dot THF) and eight salts with HBAs/DHBAs are reported. There is proton transfer from the carboxylic group of the coformer acid to the most basic nitrogen atom of the 2-aminopyrimidine ring of PAZ in all cases. Two salts were crystallized in neat form, while the remaining six are solvates and hydrates. The crystal structure of PAZ is stabilized by sulfonamide and 2-aminopyrimidine homosynthons of N-HMIDLINE HORIZONTAL ELLIPSISO and N-HMIDLINE HORIZONTAL ELLIPSISN hydrogen bonds in an R2(2)(8) ring motif. PAZ center dot HBA/DHBA salts consistently contain the aminopyridiniumMIDLINE HORIZONTAL ELLIPSIScarboxylate N+-HMIDLINE HORIZONTAL ELLIPSISO- synthon of the R2(2)(8) ring. The sulfonamide homosynthon of PAZ is disrupted in preference to the formation of N-HMIDLINE HORIZONTAL ELLIPSISO and N-HMIDLINE HORIZONTAL ELLIPSISN hydrogen bonds in salt structures. The presence of an additional basic nitrogen atom in the indazole ring of PAZ promotes hydration and solvation through the O-HMIDLINE HORIZONTAL ELLIPSISN hydrogen bond. Whereas the formation of salts is desirable for pharmaceutical formulation, the inclusion of adventitious solvent and/or water molecules with hydroxybenzoic acid coformers in the cocrystal-salt products is a limitation for this class of coformers. The stability problem faced with hydrates and solvates of PAZ center dot HBA/DHBA salts means that their formation must be carried out by strictly anhydrous procedures. The consistent occurrence of the aminopyridiniumMIDLINE HORIZONTAL ELLIPSIScarboxylate N+-HMIDLINE HORIZONTAL ELLIPSISO- ring synthon is discussed in relation to the previous results of Aakeroy, Nangia and Zaworotko groups on similar acid-base multi-component systems.